Social Economic Changes of Local Communities in Affected Locations Post-Development of Lamong Bay Terminal - Gugus Wijonarko; Amaliyah Amaliyah (Puslitbang Transportasi Antarmoda-Kementerian Perhubungan Republik Indonesia, 2022)
Infrastructure development drives changes in livelihoods, incomes, and social status. The construction of the Teluk Lamong Terminal is a phenomenon of community social change that originates from environmental changes. This study aims to explain the socio-economic changes in the surrounding community after constructing the Teluk Lamong Terminal. This research was conducted using a descriptive method by interviewing 161 employees who are also part of the local community. This study found that most people felt the socio-economic changes that occurred because of the multiplier effect in the economic field, such as opening business opportunities. In the social field, changes also occur in social relations in the community, namely the improvement in conditions of social harmony and the role of PT. Teluk Lamong Terminal in terms of repairing various infrastructures in the affected areas. Through the concept of Green Port and Green Culture, PT. Teluk Lamong Terminal also creates cultural changes in the community to participate consistently in protecting the environment.